Intimate partner violence and child maltreatment in Scotland – Insights from nationally representative longitudinal survey data. (October 2022) - Skafida, Valeria; Morrison, Fiona; Devaney, John
Abstract: Background: Research on child maltreatment in the context of intimate partner violence (IPV) rarely draws on nationally representative samples, and rarely accounts for maternal, paternal and child reports of parental aggression towards children separately. Objective: We explore if living with IPV makes children more likely to be smacked or slapped by their parents. Participants and setting: A prospective longitudinal and nationally representative child cohort study for Scotland (starting sample N:5217). Methods: Questions for children at ages 2–7 include: maternal and paternal reports of aggression towards children; children's reports of being 'smacked' by parents; maternal reports of IPV. Multivariate logit models explore how maternal IPV is associated with child maltreatment, controlling for socio-economic confounders. Results: In homes with a long-term abusive partner, children are more likely to have been smacked/slapped by the father (OR1.91, p  ≤ 0.05), mother (OR1.84 p ≤ 0.05), and both parents (OR2.31, p ≤ 0.05). Maternal IPV frequency and intensity was incrementally associated with children's odds of being smacked/slapped (OR range 1.47–1.70, p  ≤ 0.05). Ethnic minority boys were more likely (predicted probability of 42 % p ≤ 0.05) to have been smacked/slapped by their mother frequently compared to other children (predicted probability range: 19–27 %). Conclusions: When mothers report IPV, the extent and severity of the abuse is incrementally associated with children's experiences of parental aggression, and ethnic minority boys are far more at risk. Parental aggression should be understood within the context of the stresses associated with living with an abusive partner. We discuss the fragmented picture which surveys of children provide when interviewing mainly the mother. Highlights: Children living with intimate partner violence are more likely to experience parental aggression. More severe intimate partner violence is linked to greater odds of parental aggression. Ethnic minority boys are far more at risk of experiencing parental aggression. Parental aggression towards children is socially stratified.